Environmental impact of inhalers for respiratory diseases: decreasing the carbon footprint while preserving patient-tailored treatment - Sara Panigone; Federica Sandri; Rossella Ferri; Andrea Volpato; Elena Nudo; Gabriele Nicolini (BMJ Open Respiratory Research)
Patients with asthma and Chronic Obstructive Respiratory Disease (COPD) rely on three main device classes for inhalation therapy: metered-dose inhalers (MDIs), dry powder inhalers (DPIs) and soft-mist inhalers (SMIs). The carbon footprint (CF) of these inhalers differs with MDIs having a higher impact than DPIs and SMIs due to the propellant in MDIs. However, the certified CF of specific MDI products may differ significantly. MDIs still represent an essential option for many patients. Consequently, novel approaches shall be considered to balance environmental goals with patient health and well-being while maintaining a diverse range of choices for patients and physicians.